Ti-based catalyst as well as preparation method and application thereof

By loading transition metal salts and rare earth metal salts on TiO2 nanotube support, Ti-based catalysts with high catalytic performance were prepared, which solved the problems of high prices and poor thermal stability of existing catalysts, and achieved efficient catalytic oxidation and purification of NVOCs , suitable for industrial applications.

CN119236923APending Publication Date: 2025-01-03INST OF COAL CHEM CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411531270.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing catalysts have high catalytic activity but are expensive, have poor thermal stability and are too many by-products in NVOCs catalytic oxidation, making it difficult to develop a non-precious metal low-temperature oxidation catalyst with high activity, high selectivity, high stability and low price.

Method used

TiO2 nanotubes are used as support, and the transition metal salt and rare earth metal salt are loaded by impregnation. Combined with sonication, drying and high-temperature heat treatment, Ti-based catalysts with high specific surface area and pore volume are prepared to form a Ti-OH structure to enhance catalysis. performance.

Benefits of technology

It improves the catalytic performance and selectivity of the catalyst, is suitable for various working conditions, realizes efficient catalytic oxidation and thorough purification of NVOCs, has high CO2 and N2 selectivity, and is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119236923A_ABST
    Figure CN119236923A_ABST
Patent Text Reader

Abstract

The invention provides a Ti-based catalyst and a preparation method and application thereof, and belongs to the technical field of atmospheric pollutant treatment catalysts. The preparation method comprises the following steps: loading an active component precursor onto a Ti-based carrier through an impregnation method, and then carrying out first ultrasonic treatment, first drying and high-temperature heat treatment; the active component precursor comprises transition metal salt and / or rare earth metal salt. The Ti-based catalyst is prepared by the preparation method and comprises a Ti-based carrier and an active component, the Ti-based carrier is a TiO2 nanotube, and the active component comprises transition metal and / or rare earth metal; the Ti-based catalyst is applied to catalytic oxidation of NVOCs, and the reaction temperature is 80-400 DEG C. The preparation method provided by the invention is simple to operate, low in cost and convenient for industrial popularization; the prepared catalyst is large in specific surface area, can effectively improve the selectivity of CO2 and N2 when applied to catalytic oxidation of NVOCs, and is low in reaction temperature and high in purification efficiency of NVOCs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts for treating air pollutants, and in particular relates to a Ti-based catalyst and a preparation method and application thereof. Background Art

[0002] As an important precursor of ozone and PM2.5, VOCs have become a top priority in air pollution control. For the first time, they have replaced SO2 as an important indicator for assessing the effectiveness of air pollution prevention and control in various regions. Nitrogen-containing volatile organic compounds (NVOCs) are one of the typical volatile organic compounds. They are important precursors of ozone O3 and PM2.5, which can cause photochemical smog and damage human organs, including the eyes, skin, lungs, liver and nervous system. They have caused serious harm to the ecological environment and human health. Controlling them is of great significance to promoting the improvement of ecological environment quality.

[0003] At present, the methods for controlling NVOCs mainly include adsorption, catalytic oxidation, photocatalytic decomposition, biodegradation and plasma. Among them, catalytic oxidation is widely used because of its safety, high efficiency, low energy consumption, low operating temperature, high selectivity and purification efficiency. The catalysts used for catalytic oxidation of NVOCs are mainly divided into two categories: precious metal catalysts and non-precious metal catalysts. Although precious metal catalysts have high catalytic activity, they are expensive, have poor thermal stability, are prone to sintering and poisoning during the reaction, and produce too many by-products such as NO, NO2, and N2O. Therefore, developing a non-precious metal low-temperature oxidation catalyst with high catalytic activity, high selectivity, high stability and low price is a huge challenge currently faced by NVOCs management.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The object of the present invention is to provide a Ti-based catalyst and a preparation method and application thereof to solve the above problems.

[0006] In order to achieve the above objectives, the present invention particularly adopts the following technical solutions:

[0007] The present invention provides a method for preparing a Ti-based catalyst, comprising: loading an active component precursor onto a Ti-based carrier by an impregnation method, and then subjecting the Ti-based catalyst to a first ultrasonic treatment, a first drying, and a high-temperature heat treatment;

[0008] The Ti-based carrier is a TiO2 nanotube; the active component precursor includes a transition metal salt and / or a rare earth metal salt; the molar ratio of the metal atoms of the active component to the Ti atoms of the Ti-based carrier is 1:1 to 1:3;

[0009] If the molar ratio of metal atoms to Ti atoms is too small, the active components are insufficient, resulting in low catalytic activity; if the molar ratio of metal atoms to Ti atoms is too large, the active components cannot be well dispersed on the carrier and aggregate together, which will also cause a decrease in catalytic activity.

[0010] Preferably, the transition metal salt includes any one of a copper salt or a manganese salt; more preferably, copper nitrate or manganese acetate;

[0011] Preferably, the rare earth metal salt comprises a cerium salt, more preferably cerium nitrate;

[0012] Optionally, the frequency of the first ultrasonic treatment is 40KHz, and the time is 2-3h; the first drying comprises: drying in an oven at 60-80°C for 10-12h, and then drying at 100-110°C overnight; the high temperature heat treatment comprises: heating to 350-450°C at a rate of 5-10°C / min in an air atmosphere, and treating for 2-4h;

[0013] The preparation method of the TiO2 nanotubes comprises:

[0014] S1: dissolving TiO2 in an alkali solution of a certain concentration, and performing a second ultrasonic treatment for 30 to 40 minutes to obtain a mixed solution A;

[0015] S2: Transfer the mixed solution A obtained in S1 to a tetrafluoroethylene reactor, heat it to 130-150°C at a rate of 5-10°C / min, and maintain it for 36-48 hours to obtain a mixed solution B;

[0016] S3: filtering the mixed solution B obtained in S2, and soaking the solid obtained by filtration in an oxidizing solution at room temperature for 5 to 6 hours; the solid-liquid ratio (g:ml) of the solid to the oxidizing solution is 1:10 to 1:12;

[0017] Preferably, the oxidizing solution is a 2-3 mol / L H2O2 solution;

[0018] The preferred oxidizing solution concentration of the present application can generate more Ti-OH structures; the applicant has found through research that the oxidizing solution concentration and the number of Ti-OH structures are not in a simple linear relationship, and an excessively high oxidizing solution concentration not only fails to promote the generation of more Ti-OH structures, but also causes waste of reagents and increases in preparation costs. The generation of Ti-OH structures can form hydrogen bonds with DMF, thereby promoting the adsorption of DMF on the catalyst, and further promoting the flow reaction of oxygen species, forming more oxygen vacancies on the catalyst surface, promoting the activation of oxygen, and thus promoting the oxidative degradation of DMF on the catalyst surface.

[0019] S4: The solid material of S3 treated with the oxidizing solution is washed with deionized water and 2 mol / L HCl solution in sequence until it becomes neutral, and then dried in a drying oven at 100-110° C. for 36-48 hours to obtain the TiO2 nanotubes.

[0020] Optionally, the certain concentration in S1 is 8 to 10 mol / L; the alkali solution includes a NaOH solution; and the solid-liquid ratio (g:ml) of the TiO2 to the alkali solution is 1:8 to 1:10.

[0021] The present invention also provides a Ti-based catalyst prepared by the preparation method, wherein the Ti-based catalyst consists of a Ti-based carrier and an active component, wherein the Ti-based carrier is a TiO2 nanotube, and the active component includes a transition metal and / or a rare earth metal;

[0022] The specific surface area of ​​the Ti-based catalyst is 132.30-339.26 cm 2 / g, pore volume is 0.492-1.415cm 3 / g, and the average pore size is 14.9-17.6nm.

[0023] An application of the Ti-based catalyst prepared by the preparation method comprises: using the Ti-based catalyst for catalytic oxidation of NVOCs, wherein the reaction conditions are: loading the Ti-based catalyst into a fixed bed reactor, introducing O2 and DMF at the same time for reaction, and controlling the reaction space velocity at 5000 to 100000 h -1 , the reaction temperature is 80~400℃.

[0024] Beneficial effects of the present invention:

[0025] The present invention uses TiO2 nanotubes as carriers. Compared with traditional TiO2 nanotubes, the surface of the TiO2 nanotubes after further oxidation solution treatment can form a Ti-OH structure, increase the surface acidity of the catalyst, thereby enhancing the interaction with DMF and promoting the adsorption and oxidation of DMF on the catalyst. In addition, the catalyst is prepared by the classic impregnation method, which is simple and controllable, with high repeatability and great industrial application potential.

[0026] The Ti-based catalyst prepared by the method of the present invention has a larger specific surface area, pore volume and pore diameter than conventional catalysts, and the specific surface area can reach 339.26 cm 2 / g, pore volume is 0.492-1.415cm 3 / g, with an average pore size of 14.9-17.6nm, which is conducive to the adsorption, oxidation and mass transfer of pollutant molecules on the catalyst surface, and thus has higher catalytic performance.

[0027] Applied to the catalytic oxidation of NVOCs, in addition to higher catalytic performance, it also exhibits higher CO2 and N2 selectivity, with wider reaction conditions and is suitable for a variety of working environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0029] Figure 1 Scanning electron microscope images of the catalysts provided for the embodiments and comparative examples;

[0030] Figure 2 The adsorption activity evaluation diagram of the catalysts provided for the embodiments, control examples and comparative examples;

[0031] Figure 3 Raman analysis chart of the catalyst provided for the embodiments and comparative examples;

[0032] Figure 4 Fourier infrared spectrum analysis diagram of the catalyst provided for Example 3 and Comparative Example 1. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0034] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs, and the disclosure and materials cited therein are hereby incorporated by reference.

[0035] Technical equivalents to the specific embodiments described that are apparent to those skilled in the art using no more than routine experimentation are intended to be encompassed by this application.

[0036] The experimental methods in the following examples are all conventional methods unless otherwise specified. The instruments and equipment used in the following examples are all conventional laboratory instruments and equipment unless otherwise specified; the experimental materials used in the following examples are all purchased from conventional biochemical reagent stores unless otherwise specified.

[0037] Example 1

[0038] This embodiment provides a Ti-based catalyst and uses it for catalytic oxidation of NVOCs. The specific preparation method is as follows:

[0039] S1: Dissolve 1 g TiO2 in 65 mL 10 mol / L NaOH solution and treat with ultrasound for 30 min to obtain mixed solution A;

[0040] S2: The mixed solution A was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, placed in a homogeneous reactor and heated to 130°C at a rate of 5°C / min, and hydrothermally treated for 36 h to obtain a mixed solution B;

[0041] S3: After the high-temperature autoclave is cooled to room temperature, the mixed solution B is filtered and the solid is collected by centrifugation, and then treated with 2 mol / L H2O2 solution at room temperature for 5 h, with a solid-liquid mass ratio of 1:10;

[0042] S4: The solid matter of S3 treated with the oxidizing solution was washed with deionized water and 2 mol / L hydrochloric acid solution in sequence until it became neutral, and then dried in a forced air drying oven at 110° C. for 36 h to obtain TiO2 nanotubes;

[0043] S5: According to the atomic molar ratio of Mn to Ti of 1:2, the TiO2 nanotubes prepared by S4 were immersed in a manganese acetate solution, followed by ultrasonic treatment for 2 hours, dried at room temperature for 5 hours, and then dried in a forced air drying oven at 110°C for 12 hours, and then heated to 400°C in an air atmosphere at a rate of 5°C / min for 2 hours. The obtained product was recorded as MnTi catalyst.

[0044] Example 2

[0045] The difference from Example 1 is that:

[0046] S5: The TiO2 nanotubes prepared in S4 were immersed in a cerium nitrate solution at an atomic molar ratio of Ce to Ti of 1:2, followed by ultrasonic treatment for 2 hours, dried at room temperature for 5 hours, and then dried in a forced air drying oven at 110°C for 12 hours, and then heat treated at 400°C in an air atmosphere at a rate of 5°C / min for 2 hours. The obtained product was recorded as CeTi catalyst.

[0047] Example 3

[0048] This embodiment provides a Ti-based catalyst and uses it for catalytic oxidation of NVOCs. The specific preparation method is as follows:

[0049] S1: Dissolve 1 g TiO2 in 65 mL 10 mol / L NaOH solution and treat with ultrasound for 30 min to obtain mixed solution A;

[0050] S2: The mixed solution A was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, placed in a homogeneous reactor and heated to 130°C at a rate of 5°C / min, and hydrothermally treated for 36 h to obtain a mixed solution B;

[0051] S3: After the high-temperature autoclave is cooled to room temperature, the mixed solution B is filtered and the solid is collected by centrifugation, and then treated with 2 mol / L H2O2 solution at room temperature for 5 h, with a solid-liquid mass ratio of 1:10;

[0052] S4: The solid matter of S3 treated with the oxidizing solution was washed with deionized water and 2 mol / L hydrochloric acid solution in sequence until it became neutral, and then dried in a forced air drying oven at 110° C. for 36 h to obtain TiO2 nanotubes;

[0053] S5: The TiO2 nanotubes prepared in S4 were immersed in a copper nitrate solution at an atomic molar ratio of Cu to Ti of 1:2, followed by ultrasonic treatment for 2 hours, dried at room temperature for 5 hours, and then dried in a forced air drying oven at 110°C for 12 hours, and then heat treated at 400°C in an air atmosphere at a rate of 5°C / min for 2 hours. The obtained product was recorded as CuTi catalyst.

[0054] Comparative Example 1

[0055] The difference from Example 3 is that no active component is loaded, and the TiO2 nanotubes prepared by S4 are directly subjected to high-temperature heat treatment at 400°C at a rate of 5°C / min in an air atmosphere for 2 hours. The obtained product is recorded as TNTs catalyst.

[0056] Comparative Example 1

[0057] The difference from Example 3 is that steps S3 and S4 are slightly different, and the solid collected by filtering the mixed solution B is not treated with an oxidizing solution, but is directly washed, specifically:

[0058] S1: Same as Example 3;

[0059] S2: Same as Example 3;

[0060] S3: After the high temperature autoclave is cooled to room temperature, the mixed solution B is filtered and the solid matter is collected by centrifugation;

[0061] S4: The solid collected in S3 was washed with deionized water and 2 mol / L hydrochloric acid solution in sequence until it was neutral, and then dried in a forced air drying oven at 110°C for 36 h to obtain TiO2 nanotubes;

[0062] S5: The TiO2 nanotubes prepared in S4 were immersed in a copper nitrate solution at an atomic molar ratio of Cu to Ti of 1:2, followed by ultrasonic treatment for 2 hours, dried at room temperature for 5 hours, and then dried in a forced air drying oven at 110°C for 12 hours, and then heat treated at 400°C in an air atmosphere at a rate of 5°C / min for 2 hours. The obtained product was recorded as CuTi-1 catalyst.

[0063] The scanning electron microscope images of the catalysts provided in the examples and reference examples are as follows: Figure 1 As shown, Figure 1 (a) is a scanning electron microscope image of the TNTs catalyst provided in Comparative Example 1, Figure 1 (b) is a scanning electron microscope image of the MnTi catalyst provided in Example 1, Figure 1 (c) is a scanning electron microscope image of the CeTi catalyst provided in Example 2, Figure 1 (d) is a scanning electron microscope image of the CuTi catalyst provided in Example 3. Figure 1 It can be seen that the TNTs catalyst provided in Control Example 1 is a tubular structure, and the carrier TNTs in Examples 1, 2 and 3 are also tubular structures, providing a larger specific surface area for the loading of active components, and Mn, Ce and Cu are uniformly dispersed on the carrier surface.

[0064] The specific surface area S (m 2 / g)、pore volume V(cm 3 / g) and average pore diameter D (nm). The S, V and D parameters of the catalysts provided in the examples and comparative examples of the present application are shown in Table 1 below:

[0065] Table 1 Performance parameters of catalysts provided in Examples and Comparative Examples

[0066]

[0067] The catalysts provided in the examples and comparative examples of the present application were pretreated by vacuum degassing at 300° C. for 12 hours and then respectively loaded into a fixed bed reactor. The reaction temperature was set at 80-400° C. 1000 ppm DMF, 10% O2, N2 were introduced as balance gas under normal pressure, and the reaction space velocity was controlled at 30000 h -1 The catalytic performance was tested and the results were as follows Figure 2 As shown, through Figure 2It can be seen that in steady state, the DMF conversion rate of the MnTi catalyst provided in Example 1 at 240°C is 82.3%, and the N2 selectivity is 49.72%; the DMF conversion rate of the CeTi catalyst provided in Example 2 under the same conditions is 97.75%, and the N2 selectivity is 62.07%; the DMF conversion rate of the CuTi catalyst provided in Example 3 is 98.89%, and the N2 selectivity is 81.81%; the DMF conversion rate of the TNTs catalyst provided in Control Example 1 is 35.66%, and the N2 selectivity is 31.78%; the DMF conversion rate of the CuTi-1 catalyst provided in Comparative Example 1 is 72.53%, and the N2 selectivity is 48.57%.

[0068] The adsorption and desorption isotherms of N2 on the catalyst were analyzed using Quantachrome Auto Sorb iQ MP at 77 K, as well as Raman analysis. The results are shown in Table 1 and Figure 3 As shown; all catalysts in the present application have a multi-level pore structure, especially the medium and large pore structure is more prominent. Compared with traditional metal oxide catalysts, the catalysts have a larger specific surface area and pore volume, which can provide more effective adsorption sites for the adsorption of pollutants.

[0069] Figure 3 is the Raman analysis diagram of the catalyst. Figure 3 It can be seen that TNTs catalyst has a -1 (Eg), 197cm -1 (Eg), 393cm -1 (B1g) and 639cm -1 Characteristic peaks appear at (Eg), which are mainly generated by the vibration of the Ti-O structure in the catalyst lattice. This structure indicates that the Ti-OH structure may be generated on the surface of the catalyst carrier TiO2 nanotubes. This is mainly due to the oxidation treatment of the H2O2 solution during the preparation of the carrier TiO2 nanotubes, which introduces more hydroxyl structures on the TiO2 surface, thereby increasing the acidity of the surface of the carrier TiO2 nanotubes, thereby increasing the interaction between the Ti catalyst and DMF, and promoting its adsorption and oxidation on the catalyst surface. For MnTi catalyst, 146cm -1 and 400cm -1 The Raman vibration peak at 600 cm -1 The Raman vibration peaks at 152 and 400 cm-1 on the CuTi catalyst are attributed to the symmetric vibration of Mn-O in the MnO2 phase. -1 The peak at 261 cm -1 The peak at 603 cm-1 can be attributed to monoclinic CuO. -1The peak at 149 cm-1 can be attributed to the vibration peak of CuO crystal. -1 and 639cm -1 The vibration peak at 460cm -1 The Raman characteristic peak belonging to CeO2 is also clearly observed at 144 cm-1. The introduction of metal oxides forms a MO-Ti structure on the catalyst surface, affecting the vibration of the Ti-O bond. In addition, the formation of the MO-Ti structure can promote the formation of oxygen vacancies (Ov) on the catalyst surface. Studies have shown that the formation of Ov can lead to the formation of TNTs at 144 cm-1. -1 The Eg Raman peak of MnTi increases to 146 cm -1 , CuTi increases to 152 cm -1 , CeTi increases to 149cm -1 The increase in Raman shift indicates a stronger interaction between metal carriers and the catalyst, which promotes the generation of Ov. The formation of Ov is beneficial to the oxidative decomposition of VOCs, so a higher concentration of Ov in CuTi may be beneficial to the oxidation of DMF.

[0070] Figure 4 The Fourier transform infrared spectrum analysis diagram of the catalyst provided for Example 3 and Comparative Example 1. Figure 4 It can be seen that at 3440.02cm -1 The peak at 1633.80 cm-1 is attributed to the vibration peak of hydroxyl (-OH). -1 The peak indicates the presence of OH bending vibration, at 400-800 cm -1 The band between is the peak of Ti-O and Ti-O-Ti bridging mode stretching. It can be seen from the figure that after H2O2 treatment, the vibration peak of -OH red-shifted to 3425.49 cm -1 , and the -OH vibration intensity and peak area increased significantly, indicating that more Ti-OH structures may have been generated after oxidation treatment. The literature reports that the dissociation energy of this structure is much lower than that of the Ti-O structure, which can promote the flow reaction of oxygen species in the catalytic reaction, form more oxygen vacancies on the catalyst surface, promote the activation of oxygen, and thus promote the oxidative degradation of DMF on the catalyst surface.

[0071] By comparing Example 3 with Control Example 1, it can be seen that under the same other process conditions, transition metal Cu is loaded on the surface of TiO2 nanotubes by impregnation. Although the specific surface area and pore volume of the obtained catalyst decrease, it still maintains a higher specific surface area and pore volume than conventional oxide catalysts. At 240°C, the conversion rate of DMF is significantly increased from 35.66% to 98.89%, an increase of about 3 times, and the N2 selectivity is increased from 31.78% to 81.81%, achieving efficient catalytic oxidation and thorough purification of NVOCs under mild conditions. This shows that the preferred copper nitrate of the present invention has better application potential as a Ti-based catalyst for preparing catalytic oxidation of NVOCs.

[0072] By comparing Example 3 with Comparative Example 1, it can be seen that, under the same other processes, Comparative Example 1 is not treated with an oxidizing solution when preparing the carrier TiO2 nanotubes. Since more Ti-OH structures are not generated in the structure, the flow of oxygen species in the DMF catalytic reaction cannot be promoted. In Example 3, more Ti-OH structures promote the generation of oxygen vacancies in the catalyst, which is conducive to the activation of oxygen. Thus, more oxygen is involved in the reaction. First, DMF undergoes an oxidation reaction at the -CHO site on the catalyst surface to generate dimethylaminoformic acid. The CN bond of dimethylaminoformic acid is cracked to produce DMA. Subsequently, a series of CN bond cracking and oxidation reactions occur in DMA on the catalyst surface to produce NH3 and NOx, and CO2 is produced at the same time. NOx further reacts with NH3 to generate N2, achieving a thorough purification of DMF.

[0073] Please note that the technical features of the above embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above embodiments only express several implementation methods of the present application, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several variations and improvements can be made, which all belong to the scope of protection of the present application. Therefore, the scope of protection of the patent in this application shall be based on the attached claims.

Claims

1. A method for preparing a Ti-based catalyst, characterized in that: include: The active component precursor is loaded onto the Ti-based carrier by an impregnation method, and then subjected to a first ultrasonic treatment, a first drying, and a high-temperature heat treatment to obtain the Ti-based catalyst; The active component precursor includes a transition metal salt and / or a rare earth metal salt.

2. The preparation method according to claim 1, characterized in that: The molar ratio of the metal atoms of the active component to the Ti atoms of the Ti-based carrier is 1:1 to 1:

3.

3. The preparation method according to claim 1, characterized in that: The Ti-based carrier is TiO2 nanotube.

4. The preparation method according to claim 3, characterized in that: The preparation method of the TiO2 nanotubes comprises: S1: dissolving TiO2 in an alkali solution of a certain concentration, and performing a second ultrasonic treatment for 30 to 40 minutes to obtain a mixed solution A; S2: Transfer the mixed solution A obtained in S1 to a tetrafluoroethylene reactor, heat it to 130-150°C at a rate of 5-10°C / min, and maintain it for 36-48 hours to obtain a mixed solution B; S3: Filter the mixed solution B obtained in S2, and immerse the solid obtained by filtration in an oxidizing solution at room temperature for 5 to 6 hours; S4: The solid material of S3 treated with the oxidizing solution is washed with deionized water and 2 mol / L HCl solution in sequence until it becomes neutral, and then dried in a drying oven at 100-110° C. for 36-48 hours to obtain the TiO2 nanotubes.

5. The preparation method according to claim 4, characterized in that: In the step S3, the solid-to-liquid ratio (g:ml) of the solid matter to the oxidizing solution is 1:10 to 1:

12.

6. The preparation method according to claim 4 or 5, characterized in that: The oxidizing solution is a 2-3 mol / L H2O2 solution.

7. The preparation method according to claim 4, characterized in that: The preparation of the TiO2 nanotubes also satisfies one or more of the following conditions: a. The certain concentration in S1 is 8 to 10 mol / L; b. The alkali solution comprises a NaOH solution; c. The solid-liquid ratio (g:ml) of the TiO2 to the alkali solution is 1:8 to 1:

10.

8. The preparation method according to claim 1, characterized in that: The preparation method of the Ti-based catalyst also satisfies one or more of the following conditions: d. The frequency of the first ultrasonic treatment is 40KHz and the time is 2 to 3h; e. The first drying comprises: drying in an oven at 60 to 80 ° C for 10 to 12 hours, and then drying at 100 to 110 ° C overnight; f. The high temperature heat treatment comprises: heating to 350-450°C at a rate of 5-10°C / min in an air atmosphere for 2-4h; g. The transition metal salt comprises any one of a copper salt or a manganese salt; h. The rare earth metal salt includes a cerium salt.

9. A Ti-based catalyst prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The Ti-based catalyst is composed of a Ti-based carrier and an active component, wherein the Ti-based carrier is a TiO2 nanotube, and the active component includes a transition metal and / or a rare earth metal; The specific surface area of ​​the Ti-based catalyst is 132.30-339.26 cm 2 / g, pore volume is 0.492-1.415cm 3 / g, and the average pore size is 14.9-17.6nm.

10. An application of a Ti-based catalyst prepared by the preparation method according to any one of claims 1 to 8, characterized in that: include: The Ti-based catalyst is used for catalytic oxidation of NVOCs. The reaction conditions are as follows: the Ti-based catalyst is loaded into a fixed bed reactor, and O2 and DMF are introduced simultaneously for reaction. The reaction space velocity is controlled at 5000 to 100000 h -1 , the reaction temperature is 80~400℃.